VIABILIDADE ECONÔMICA SOJA-HORTALIÇA ADUBADA ORGANICAMENTE NA REGIÃO DO ECÓTONO CERRADO-PANTANAL - Sakissaka, Roberto Carlos Seiji; Ribera, Laura Matos; Cardoso, Reginaldo de Moraes; Secco, Sanara Karoline C; Silva, Maiele Leandro (ANAIS DO ENIC, 2018)
-